Working Capital of Kampoeng Batik Jetis Sidoarjo SMEs in East Java - Istanti, Lulu Nurul; Linarki, Marshalia Dwi (KnE Social Sciences, 2021)
The purpose of this study was to examine the source and use of working capital at Kampoeng Batik Jetis Sidoarjo SMEs. It was conducted using a qualitative descriptive method. The results showed that the source of working capital was mainly personal, such as family money, savings and ploughing back profits. Funders and formal financial institutions such as banks did not play significant roles in financing SMEs due to the complexity of credit procedures and requirements. The use of working capital was limited to the purchase of raw materials and wage payments. Keywords: Working Capital, SMEs, Kampoeng Batik Jetis Sidoarjo